Contributions to the morphology and histology of the genital system of Limax valentianus. (Ferussac) (Pulmonata: Limacidae.) - Stears, Michèle (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1974.